Meningkatkan Partisipasi Aktif dan Hasil Belajar IPS Siswa melalui Penerapan Model Pembelajaran Kooperatif Group Investigation pada Siswa Kelas VIII-6 SMP Negeri 1 Sei Bingai Tahun Pelajaran 2018-2019 - Marni Kemit (Keguruan, 2022)
This study is a type of Classroom Action Research (CAR) that aimed to increase the active participation and learning outcomes for Social Science (IPS) subjects in class VIII-6 SMP Negeri 1 Sei Bingai in 2018-2019 through the application of the Group Investigation (GI) cooperative learning model. This study used the research methods from Kemmis and Taggart. The data collection techniques used are tests, observations and documentation. The test instrument used in the form of multiple choice questions and observation sheets consist of indicators of student active participation. The result showed that in the pre-cycle, the percentage of completeness was 40.6%, increasing in the first cycle to 87.5% and reaching 93.75% in the second cycle. The active participation also experienced an increasing in each cycle where in the first cycle active participation and the second cycle in the Good category. Based on the results of the Group Investigation (GI) cooperative learning model research, the active participation and Social Science learning outcomes for class VIII-6 students of SMP Negeri 1 Sei Bingai for the 2018-2019 academic year have increased.